Regeneración Ecológica del Centro Experimental Salache - Páez Tapia, Enrique Javier (2016)
The aim of the project was aimed to characterize certain goods and eco systemic services which account Salache Experimental Center, located in the parish Eloy Alfaro, Canton Latacunga, Cotopaxi Province. the use of water, soil, vegetation and wildlife present was characterized to develop from this recovery alternatives for the CEYPSA of areas identified as desert areas and relegated campus campus. For this project the following documentation collection: 1) Diagnosis of the current ecosystem through inventories 3 investigations already carried 2) Literature review. Based on data compiled and the results obtained proposals based on two concepts, Waste Reduction Ecological Recovery and developed. These proposals are: a) Restoration of the lagoon of the institution in order to regenerate this resource as a recreation area. b) Dynamics Waste Management campus.